Gastrointestinal nematodes and anthelmintic resistance in Danish goat herds☆ - Holm Signe A.; Sörensen Camilla R. L.; Thamsborg Stig M.; Enemark Heidi L. (Parasite, 2014)
The prevalence of gastrointestinal parasites in Danish goats and the presence of anthelmintic resistance (AR) in 10 selected herds were investigated during April–September 2012. All Danish herds (n = 137) with 10 or more adult goats were invited to participate, and of these 27 herds met the inclusion criterion of more than 10 young kids never treated with anthelmintics. Questionnaire data on management were collected, and faecal samples from 252 kids were analysed by the McMaster technique. From all herds with a mean faecal egg count (FEC) above 300 eggs per g of faeces, pooled samples were stained with peanut agglutinin (PNA) for specific detection of Haemonchus contortus. Strongyle eggs were detected with an individual prevalence of 69%, including Nematodirus battus (3.6%) and other Nematodirus species (15.0%). Eimeria spp. were observed in 99.6% of the kids. H. contortus was found in 11 of 12 (92%) tested herds. Anthelmintics were used in 89% of the herds with mean treatment frequencies of 0.96 and 0.89 treatments per year for kids and adults, respectively. In 2011, new animals were introduced into 44% of the herds of which 25% practised quarantine anthelmintic treatments. In 10 herds the presence of AR was analysed by egg hatch assay and FEC reduction tests using ivermectin (0.3 mg/kg) or fenbendazole (10.0 mg/kg). AR against both fenbendazole and ivermectin was detected in seven herds; AR against fenbendazole in one herd, and AR against ivermectin in another herd. In conclusion, resistance to the most commonly used anthelmintics is widespread in larger goat herds throughout Denmark.